To simplify the expression, we can use the rules of exponents.
First, multiply the coefficients 8 and 4 to get 32:
(8p^-5q^5)(4p^-3q^-2) = 32p^-5p^-3q^5q^-2
Next, simplify the variables with the same base, p. Since we have p^-5 and p^-3, we can add their exponents together: p^-5p^-3 = p^(-5-3) = p^-8
Similarly, for the variables with the same base, q, we can add their exponents together: q^5q^-2 = q^(5-2) = q^3
Putting it all together, we have: 32p^-5p^-3q^5q^-2 = 32p^-8q^3
Therefore, the simplified expression with positive exponents is 32p^-8q^3.
Simplify the expression. Write your answer with positive exponents only. (8p^-5q^5)(4p^-3q^-2)
1 answer